2020
DOI: 10.1016/j.reprotox.2020.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Data integration, analysis, and interpretation of eight academic CLARITY-BPA studies

Abstract: Consortium Linking Academic and Regulatory Insights on BPA Toxicity" (CLARITY-BPA) was a comprehensive "industry-standard" Good Laboratory Practice (GLP)-compliant 2-year chronic exposure study of bisphenol A (BPA) toxicity that was supplemented by hypothesis-driven independent investigator-initiated studies. The investigator-initiated studies were focused on integrating disease-associated, molecular, and physiological endpoints previously found by academic scientists into an industry standard guideline-compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 244 publications
(376 reference statements)
1
37
0
Order By: Relevance
“…A study by Prins and co-workers in 2018 using NCTR, Sprague-Dawley cesarean-derived rats, and prostate epithelial cells proposed that BPA exposure can increase the risk of aging-associated cancers such as PC (Prins et al 2018 ). To have better clarity on the CLARITY-BPA studies’ findings, Heindel and co-workers consolidated the findings of various studies (Heindel et al 2020 ). The same report proposes that BPA exposure during development can adversely affect multiple organs’ functioning (Heindel et al 2020 ).…”
Section: Clarity-bpa Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Prins and co-workers in 2018 using NCTR, Sprague-Dawley cesarean-derived rats, and prostate epithelial cells proposed that BPA exposure can increase the risk of aging-associated cancers such as PC (Prins et al 2018 ). To have better clarity on the CLARITY-BPA studies’ findings, Heindel and co-workers consolidated the findings of various studies (Heindel et al 2020 ). The same report proposes that BPA exposure during development can adversely affect multiple organs’ functioning (Heindel et al 2020 ).…”
Section: Clarity-bpa Studymentioning
confidence: 99%
“…To have better clarity on the CLARITY-BPA studies’ findings, Heindel and co-workers consolidated the findings of various studies (Heindel et al 2020 ). The same report proposes that BPA exposure during development can adversely affect multiple organs’ functioning (Heindel et al 2020 ). Besides, as per the CLARITY-BPA core study, BPA at a dose of 2.5 μg/kg/day induced adenocarcinoma of the mammary gland.…”
Section: Clarity-bpa Studymentioning
confidence: 99%
“…Thus the analysis by the NTP could not confirm the low-dose NMDR hypothesis for BPA even with the most thorough repeated-dose and chronic studies ever done on BPA and analyzing a comprehensive range of classical toxicological endpoints. (ii) The laboratories testing non-guideline endpoints found mixed results, some claiming evidence of low-dose NMDR (Heindel et al 2020). The claimed NMDR occurred at different doses, depending on the endpoint, and had W-, Z-or U-forms-in most cases individual doses anywhere in the dose range showed a signal which was considered biologically relevant by the authors, although from a traditional statistical viewpoint, these curves would rather be interpreted as spurious or erratic.…”
Section: Science's First Principle: Replicationare Low-dose Nmdr Effects Replicated In Independent Repetitions?mentioning
confidence: 99%
“…(See also below about the EFSA opinion on NMDR for CLAR-ITY-BPA). Some high-level comparison to previous studies was given in Table 5 in the recent review on the studies investigating non-guideline endpoints (Heindel et al 2020), however this Table indicated whether effects at any dose on an organ were seen, not whether the same dose triggered the same effect on the same measurement parameter as observed before. Although the CLARITY-BPA study was conducted blinded, some of these assessments are post hoc analyses after un-blinding.…”
Section: Science's First Principle: Replicationare Low-dose Nmdr Effects Replicated In Independent Repetitions?mentioning
confidence: 99%
“…In addition, Camacho et al (2019) presented a summary of the core study data but included a more expansive discussion of the FDA's conclusions. An integrated analysis of findings from eight CLARITY-BPA grantee studies has also been published (Heindel et al 2020); however, this paper is not summarized in this report.…”
Section: Executive Summarymentioning
confidence: 99%